Variability in Asoka (Saraca Asoca(Roxb.) de wilde) - Vidhu Francis Palathingal (Department of Plant Breeding and Genetics, College of Horticulture, 2010)
Asoka (Saraca asoca) is a sacred tree among the Buddhists and Hindus. It is called sorrow-less tree as it removes the grief. The tree has immense medicinal properties. Its bark is mainly used for correcting uterine problems. The well-known Ayurvedic preparations of asoka bark are Asokarishtam and Asokaghrutham. Due to over exploitation of this tree for its bark, this has now become almost extinct. The International Union for Conservation of Nature and Natural Resources (IUCN) has listed this species under ‘globally vulnerable’ category. It is also enlisted among the 36 threatened and endangered medicinal plants of India. Due to its acute short supply compared to its demand, various development and research activities are being prioritized to conserve, utilize and improve this species. Therefore the present study was undertaken to assess morphological variations in existing germplasm and to study the reproductive biology of S. asoca. Collection of seeds and evaluation of seed and seedling traits, evaluation of therapeutical components and molecular characterisation of asoka were the other objectives of the study. Variability studies for morphological traits of asoka indicated that height of plant and stem girth have high correlation with bark yield as well as higher direct effect. These traits can be used for identifying better genotypes for higher bark yield. In discriminant function analysis, the selection index involving height of plant along with bark yield constituted for selection criteria among asoka genotypes. Using this selection index, accessions IC566463, IC566489, IC566488, IC566482 were selected as better accessions for higher bark yield. The 43 accessions maintained in germplasm of asoka at AICRP on M&AP were grouped into two major clusters based on morphological traits. These clusters further formed 6 clusters. Accession IC566488 grouped alone in one cluster indicated that this accession was different from all other accessions. In all the other 5 clusters, accessions from Thrissur was included. This indicated that accessions did not follow geographical distributions. Some of the accessions from Thrissur may have relationship with accessions from other districts. Reproductive biology of asoka was studied. It indicated that the reproductive traits like floral biology, anthesis, pollen morphology, its viability have variability among eight trees studied in KAU campus. Among the eight trees studied, ‘KAU8’ have better reproductive traits compared to the rest. Preliminary studies were carried out in pollination system and agents for pollination in asoka. The studies indicated that ants may be one of the pollinating agents. Seed and seedling behaviour of asoka were studied on seeds collected from 80 trees located in different districts of Kerala. Seed breadth, seed volume, height of plant and stem girth were identified as selection traits for better seedlings. Hence at seed stage, bigger sized seeds with higher seed volume will result into better seedlings. Vigorous seedlings is produced from tall seedlings with higher stem girth and in mature plants for higher bark yield, height of plant and stem girth can be selection traits. Thus the selection parameters were worked out in three stages in asoka. Based on seed and seedling selection parameters, OKL4, OKL2 from Odakkali, KKL2 from Kottakkal and TVM2 from Thiruvananthapuram were selected as better mother plants for higher bark yielding accessions. The biochemical constituents (phenol and tannin content) imparting medicinal properties were estimated among the different age groups of asoka. Both phenol and tannin contents were higher in bark compared to flower and leaves. About 50 per cent of therapeutical constituents are available in flowers and hence at non destructive level, flowers of asoka can be substituted for bark. The trees KAU8, KAU7, KAU6 and among the accessions IC566474, IC566467 and among the seedlings VKA6, VKA7, VKA8, KMK3 indicated higher phenol and tannin content compared to rest. Molecular characterisation among the selected asoka accessions representing the different districts of Kerala were studied. RAPD analysis was attempted among ten accessions selected. Dendrogram was constituted based on pooled RAPD data. The ten selected accessions were grouped into two major clusters as done in morphological grouping. In grouping at molecular level, the accession IC566488 kept apart as a single group indicating the same trend at its morphological level.The clustering pattern based on molecular characterisation did not follow geographical distribution of accessions.